RECONSTRUCTION OF BASIC KNOWLEDGE ON LEARNING BIPA FOR DEVELOPING PROFESSIONALISM OF BIPA TEACHERS - Suyitno, Imam (IJRDO- Journal of Educational Research, 2017)
This study aims to describe aspects of learning Indonesian for foreign students (BIPA) that need to be understood by someone who will teach BIPA. The basic knowledge can be utilized by the teacher to select teaching-learning strategies and teaching materials that required by BIPA students. To gain those understanding, this study effort to collect data about an information on the implementation of learning BIPA from the real class of teaching-learning BIPA. By using a qualitative approach with a model of ethnographic analysis, the study obtain findings that (a) foreign students studying BIPA has characteristics that different both in terms of learning styles and cultural backgrounds, (b) the implementation of learning BIPA more emphasis on the communicative considering learning styles of BIPA students, (c) learning approach of BIPA need to consider to the norms of pedagogical of language learning for adult learners so that the topic of language teaching materials must be selected based on the needs of adults in communication, and (d) the cultural aspects in the form of cultural knowledge, cultural behaviors, and cultural objects made as teaching material in learning BIPA by using a variety of learning techniques